Postmenopausal hyperandrogenism - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2022)
Postmenopausal hyperandrogenism is a state of relative or absolute androgen excess originating from the adrenal glands and/or ovaries clinically manifested by the presence of terminal hair in androgen-dependent areas of the body, and other manifestations of hyperandrogenism such as acne and alopecia or the development of virilization. In such circumstances, physicians must exclude the possibility of rare but serious androgen-producing tumors of the adrenal glands or ovaries. Worsening of undiagnosed hyperandrogenic disorders such as polycystic ovary syndrome, congenital adrenal hyperplasia, ovarian hyperthecosis, Cushing syndrome and iatrogenic hyperandrogenism should be considered for differential diagnosis. Elevated serum testosterone not only causes virilizing effects, but also will lead to hypercholesterolemia, insulin resistance, hypertension and cardiac disease. An ovarian androgen-secreting tumor, which is diagnosed in 1-3 of 1000 patients presenting with hirsutism, comprises less than 0.5% of all ovarian tumors. Adrenal tumors, including non-malignant adenomas and malignant carcinomas, are less common than ovarian tumors but cause postmenopausal virilization. Measurement of serum testosterone, sex hormone-binding globulin, dehydroepiandrosterone sulfate, androstenedione and inhibin B is necessary in postmenopausal women with the complaints and signs of hyperandrogenism. Some tests to discard Cushing syndrome should also be done. After an etiological source of androgen hypersecretion has been suspected, we recommend performing magnetic resonance imaging of the adrenal glands or ovaries. Medical management with gonadotropin-releasing hormone agonist/analogues or antagonists has been reported for women who are either unfit for surgery or in whom the source of elevated testosterone is unidentified.
Keywords: Postmenopausal; hyperandrogenism; androgen-secreting ovarian tumor; hyperthecosis; adrenal tumor; POLYCYSTIC-OVARY-SYNDROME; LEYDIG-CELL TUMOR; ANDROGEN EXCESS; ADRENAL-HYPERPLASIA; ADRENOCORTICAL CARCINOMA; SERUM TESTOSTERONE; FOLLOW-UP; WOMEN; HYPERTHECOSIS; DIAGNOSIS